Realizing multiculturalism and social integration in Banuroja community - Noe, Wahyudin; Wardhani, Novia Wahyu; Umar, Sitirahia Hi; Yunus, Rasid (Universitas Negeri Yogyakarta, 2021)
There have been many studies concerning Banuroja; however, there is always something novelty in creating a role model for village-based character education where the aim is to create a multicultural society into a multicultural community. This study examines community activities related to the national character values that embody multiculturalism and social integration in the Banuroja community. The method was qualitative with an ethnographic approach. Data were obtained from observations, interviews, and documentation carried out during 2019-2020. The validity of the data used triangulation, member checks, prolonged time, and peer debriefing. While the data analysis technique used ethnographic data analysis, namely describing, analyzing, and interpreting. The result shows that the realization of multiculturalism and social integration in the Banuroja community is carried out using three ways of assimilation, tolerance in beliefs/religions, appreciating other ethnic/religious activities by attending, and mutual cooperation. Guidance is also carried out through national and religious activities in the community, advice from parents in the family, and civic education in the schools, exemplary by community leaders, including ethnic, religious, and youth leaders.